2007
DOI: 10.1194/jlr.m700271-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Isomers of conjugated linoleic acids are synthesized via different mechanisms in ruminal digesta and bacteria

Abstract: Digesta samples from the ovine rumen and pure ruminal bacteria were incubated with linoleic acid (LA) in deuterium oxide-containing buffer to investigate the mechanisms of the formation of conjugated linoleic acids (CLAs). Rumenic acid (RA; cis-9,trans-11-18:2), trans-9,trans-11-18:2, and trans-10,cis-12-18:2 were the major CLA intermediates formed from LA in ruminal digesta, with traces of trans-9, cis-11-18:2, cis-9,cis-11-18:2, and cis-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
139
1
12

Year Published

2008
2008
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(164 citation statements)
references
References 48 publications
12
139
1
12
Order By: Relevance
“…Concentrations of trans-10,cis-12-CLA were too low in the mixed microbiota to make an assessment of labelling, but data from incubations of LA with pure cultures indicated that the labelling of trans-10,cis-12-CLA was much lower compared with RA. This is a pattern that has been observed previously in pure and mixed cultures of ruminal bacteria (Kepler et al, 1971;Wallace et al, 2007).…”
Section: Fatty Acid Biohydrogenation By Human Gut Bacteriasupporting
confidence: 63%
“…Concentrations of trans-10,cis-12-CLA were too low in the mixed microbiota to make an assessment of labelling, but data from incubations of LA with pure cultures indicated that the labelling of trans-10,cis-12-CLA was much lower compared with RA. This is a pattern that has been observed previously in pure and mixed cultures of ruminal bacteria (Kepler et al, 1971;Wallace et al, 2007).…”
Section: Fatty Acid Biohydrogenation By Human Gut Bacteriasupporting
confidence: 63%
“…Fish oil or marine algal oil rich in long chain polyunsaturated fatty acids (PUFA) in the diet are known to inhibit the complete biohydrogenation of C18 unsaturated fatty acids resulting in an increase in ruminal trans 18:1 and trans 18:2 outflow Kim et al, 2008;Lee et al, 2008). Incubations with rumen micro-organisms have shown that eicosapentaenoic acid (EPA; cis-5, cis-8, cis-11, cis-14, cis-17 20:5) and docosahexaenoic acid (DHA; Figure 2 Putative pathways describing cis-9, cis-12 18:2 metabolism in the rumen (adapted from Harfoot and Hazlewood, 1988;Hudson et al, 1998;Wallace et al, 2007;Shingfield et al, 2008a). Arrows with solid lines highlight the major biohydrogenation pathway, whereas arrows with dashed lines describe the formation of minor fatty acid metabolites.…”
Section: Ruminal Lipid Metabolismmentioning
confidence: 99%
“…Trans-10, cis-12 CLA formed during the isomerization of LA (Wallace et al, 2007) is the only biohydrogenation intermediate to have been infused at the abomasum over a range of doses and shown unequivocally to inhibit milk fat synthesis in the bovine. Often increases in ruminal trans-10, cis-12 CLA production have been considered as the cause of MFD, but direct measurements indicate that ruminal outflow of trans-10, cis-12 CLA in lactating cows is less than 1.5 g/day (Shingfield and Griinari, 2007; Table 3).…”
Section: Role Of Ruminal Biohydrogenation On Mammary Lipogenesis In Tmentioning
confidence: 99%
“…Most dietary FA are esterified, and they are almost completely hydrolyzed to free FA in the rumen. Unsaturated free FA are then isomerized (double-bond position or orientation changed) and reduced (saturation of double bond), although the exact mechanisms are not well established (Wallace et al, 2007). The resulting saturated FA and some of the biohydrogenation intermediates escape the rumen and are subsequently absorbed.…”
Section: Biohydrogenation Intermediatesmentioning
confidence: 99%